Analisis Pelaksanaan Vaksinasi Booster di Puskesmas Kota Jambi - Novia Anggraini; Dianita Ekawati; Akhmad Dwi Priyatno (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The World Health Organization together with the Government have declared Covid-19 as a Global Pandemic and declared Corona Virus Disease 2019 (Covid-19) as a health emergency. In an effort to prevent the spread of the Covid-19 virus, the Indonesian government has vaccinated all elements of society. It is known that the implementation of booster vaccination is still very low, especially in adolescents. In the implementation process, there are still many people who do not dare to vaccinate because of massive hoaxes spread on social media. This study aims to determine the analysis of the implementation of booster vaccination at the Tanjung Pinang Health Center Jambi City in 2022. It was carried out in June 2022. This study was quantitative with a cross sectional design, the population of this study was the entire community at the Tanjung Pinang Health Center totaling 96 samples. Data collection and retrieval using a questionnaire. The results of statistical test analysis using Chi-Square statistical tests and multiple logistic regression where the results showed there was a significant relationship (p value <0.05) for the variables age (0.021), gender (0.029), motivation (0.000), vaccine availability (0.003 ), and community participation (0.000). There is no relationship between the variables of education (0.503), occupation (0.240), and support for health workers (0.251). From the results of multivariate statistical tests, it was found that the dominant factor in implementing booster vaccination was community participation (p= 0.004; OR= 6.089). It is recommended to pay attention to community participation in the implementation of booster vaccination activities involving religious leaders, community leaders and local traditional leaders.